NEUROCIENCIA EDUCATIVA Y SU IMPACTO EN EL RENDIMIENTO ACADÉMICO DE ESTUDIANTES DE EGB - VELASCO CARCAMO ANA GABRIELA (2024)
This study focused on examining how educational neuroscience and its principles impact the academic performance of fourth-grade students in Basic General Education at Jaime Collantes Yánez School. The research addressed the complexity of this topic through the application of a variety of methods, including surveys, interviews, and classroom observations. Neurodidactic strategies were incorporated during a specific period to assess their effectiveness in improving student performance. The results revealed a significant improvement in students' academic performance after the implementation of these strategies, indicating greater engagement, participation, and understanding of the content. This improvement suggests a positive relationship between the application of neuroeducational strategies and students' academic success. This study supports the notion that educational neuroscience can be an effective tool to optimize the learning process in the classroom. The findings of this research underscore the importance of integrating neuroscience-based approaches into pedagogical practice to promote stronger academic performance among students. In an ever-evolving educational context, understanding and applying the principles of neuroscience are essential to address students' individual needs and promote more meaningful and lasting learning.